Quantitative inheritance of leaf shape characters in tobacco (Nicotiana tabacum L.) : a thesis presented in partial fulfilment of the requirements for the degree of Master of Agricultural Science in Plant Science at Massey University, Palmerston North, New Zealand - Yaacob, Musa bin (Massey University, 1982)
An F₁ half diallel cross experiment with 8 parents (i.e. ½ p (p = 1) combinations) was used to study the quantitative inheritance of leaf shape characters in tobacco (Nicotiana tabacum L.). The effect of stalk positions on the inheritance of these characters was also included. The study was carried out under a glasshouse conditions. The parental lines used in the crosses represent a random sample of leaf shape characters available in New Zealand germplasm collection. Except for wing area (2nd leaf), phenotypic analysis showed that there was a high genetic variability for other characters. The genetic analysis of the diallel indicated that inter-locus interaction (epistasis) was of little importance for most of the characters studied. Additive genetic variance was the main component of the total genetic variance. Heritability estimates ranged from moderate (approximately 40 %) to moderately high (approximately 70 %) for most characters. Near similar values were obtained from both the narrow and broadsense heritability estimates. Very little hybrid vigour was observed for both leaf area and leaf dry weight. Both the phenotypic and genotypic correlation coefficients between selected pairs of characters were in good agreement with each other in terms of direction and levels of significance. The estimates were generally high and highly significant. The components of genetic variance (i.e. additive and dominance genetic variance), heritability and correlation coefficient estimates were generally larger in the middle as compared to the top or bottom leaves.
Keywords: Tobacco; Genetics